Sexual Harassment in Higher Academic Institutions in J&K: AStudy of Preclusion and Corrective Mechanism (International Journal of Food and Nutritional Sciences, 2022)
Ubiquitously in the globe, sexual harassment is recognised as an infringement on human rights. It is classified as a crime. It insults the honour and dignity of a woman as a person. The sexual harassment results in violation of the basic fundamental rights of women particularly their right to equality under articles 14 and 15 of the Indian constitution and their right to life and to live with dignity under article 21. An egregious violation of a woman’s right to equality and respect is sexual harassment. Any instance of sexual harassment against a woman in a place of education is a violation of both her human and constitutional rights. It fosters a hostile and insecure climate which discourages women’s participation in higher education thereby adversely affecting their economic empowerment and the goal of inclusive growth. It is belligerent at a very individual level and in a way demoralizes the right to equal opportunity and equal treatment of women in the educational institutions. Sexual harassment is characterised as unwelcome and sexually exploitative behaviour. It may take many different forms, including physical contact, excessive demands for sexual favours, and statements with sexual overtones directed towards a possible victim. It also covers behaviours like leering, cracking crude jokes, making sexual comments about someone’s attire, physique, or attractiveness, as well as verbal or nonverbal sexual misbehaviour. Higher education institutions are the forerunners in highlearning and are intended to provide a secure atmosphere in which faculty, staff, and students may pursue their academic objectives. Sexual harassment is still seen as an issue at these institutions of higher learning, despite the fact that they provide a favourable and welcoming environment for the teaching and learning process. The present study tries to examine the legal framework and scrutiny the prevention and redressal Mechanismof sexual harassment in higher education institutions in Jammu and Kashmir.